2020
DOI: 10.1049/iet-sen.2020.0084
|View full text |Cite
|
Sign up to set email alerts
|

Literature survey of deep learning-based vulnerability analysis on source code

Abstract: Vulnerabilities in software source code are one of the critical issues in the realm of software code auditing. Due to their high impact, several approaches have been studied in the past few years to mitigate the damages from such vulnerabilities. Among the approaches, deep learning has gained popularity throughout the years to address such issues. In this literature survey, the authors provide an extensive review of the many works in the field software vulnerability analysis that utilise deep learning‐based te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 63 publications
0
7
0
Order By: Relevance
“…In recent years, China's nancial auditing of colleges and universities has been developed in an unprecedented way by combining national conditions, absorbing international advanced ideas, and groping on the road of practice, constantly improving and re ning. With the ourishing development of computer science and technology, audit informatization has become a wave that promotes the development and progress in the eld of nancial auditing in universities, improving audit e ciency, and saving audit costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, China's nancial auditing of colleges and universities has been developed in an unprecedented way by combining national conditions, absorbing international advanced ideas, and groping on the road of practice, constantly improving and re ning. With the ourishing development of computer science and technology, audit informatization has become a wave that promotes the development and progress in the eld of nancial auditing in universities, improving audit e ciency, and saving audit costs [1].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, they reviewed 61 primary studies, published up to February 2021, and explored the data requirements, collection, labeling and cleaning processes, also discussing the challenges of these processes. Semasaba et al presented a systematic literature review of software vulnerability analysis on source code using Deep Learning (DL) [5]. They retrieved 28 papers published between 2014 and 2020 by searching on six widely used Digital Libraries for studies about software vulnerability detection.…”
Section: Related Workmentioning
confidence: 99%
“…To the best of our knowledge, only two studies have been published that focus on systematically reviewing SVP research and knowledge: Semasaba et al [17], and Hasif et al [4]. The former exclusively investigated Deep Learning techniques, whereas the latter provided a wider view of SV detection, including non-learning based techniques.…”
Section: Existing Svp Reviewsmentioning
confidence: 99%
“…The SV data used to train a model is the most imperative component of this data-driven process. Although most studies have reported data preparation and data quality as significant issues for this research area [4], [10], [13], [16], [17], [24], they have not performed in-depth analysis of the data quality in SVP research to determine the encountered issues or potential solutions. This knowledge gap fails to provide practitioners and researchers with the specific insights needed to remediate data quality issues.…”
Section: Existing Svp Reviewsmentioning
confidence: 99%
See 1 more Smart Citation